Production of bioabsorbible nanoparticles of polycaprolactone by using a tubular recirculating system - Gabriel Jaime Colmenares-Roldan; Liliana Maria Agudelo-Gomez; Rodolfo Pinal; Lina Marcela Hoyos Palacio (Dyna, 2018)
Encapsulation and controlled release of substances using polymeric nanoparticles require that these have a high reproducibility, homogeneity, and control over their properties, especially when they are to be used in medical, pharmaceutical or nutritional applications among others. This work shows a high productivity system to synthesize nanoparticles in an easy, fast and controlled way. This study shows the effect of molecular weight of the polymer, the type of surfactant and the relationship between the volumes of the aqueous and the organic phases. It was found that the first two variables have a statistically significant effect on the diameter of the nanoparticles while the relationship between the volume of the aqueous phase and the organic phase does not significantly affect the diameter of the nanoparticles. Additionally, it was found that none of the three variables significantly affects the polydispersity index (PI) of the nanoparticles.